Analysis of Influencing Factors of Family Resilience in Children with Congenital Tibial Pseudoarthrosis - Xie JH; Mei HB; Ouyang YQ; Huang Y; Liu K; Zhu GH; Hou ST; Wang LY (Dove Medical Press, 2022)
Jian-Hui Xie, Hai-Bo Mei, Ya-Qi Ouyang, Yuan Huang, Kun Liu, Guang-Hui Zhu, Shu-Ting Hou, Lan-Ying Wang Department of Orthopedics, Hunan Children's Hospital, Changsha, 410007, People's Republic of ChinaCorrespondence: Hai-Bo Mei, Department of Orthopedics, Hunan Children's Hospital, No. 86 of Ziyuan Street, Yuhua District, Changsha, 410007, People's Republic of China, Tel +86 139 7519 7731, Fax +86 731-85356666, Email mei_haibo@yeah.netAim: To investigate the status of the family resilience score of caregivers of children with congenital pseudarthrosis of the tibia (CPT) and analyse its influencing factors to provide a reference and basis for clinical formulation of a family resilience intervention programme.Methods: A total of 379 families of children with CPT were included in this study, which used a combination questionnaire to investigate the families of children with CPT. The researchers sent a link to the questionnaire to all eligible subjects to conduct a survey on the characteristics of families of children with CPT. Single factor analysis was used to compare the total scores of family resilience. Multiple linear regression was used to determine meaningful variables for single factor analysis.Results: The average family resilience score was 151.79 ± 30.79, the lowest score was 20 and the highest score was 231. The CPT usually occurred in unilateral limbs (37.63%). The payment methods of medical expenses were through a rural cooperative medical system (44.85%). The caregivers were mostly the mothers (62.80%) and caregivers were 31- 40 years old (62.27%). Most caregivers were farmers (30.34%). The average monthly income of the families in the past year was 1000- 5000 yuan (54.09%). There were significant differences in family resilience scores between caregivers' working conditions (P = 0.039) and average monthly incomes in the past year (P = 0.008). The working conditions of caregivers and the average monthly income of families in the past year were the main factors affecting the family resilience of caregivers of children with CPT.Conclusion: The caregivers' working conditions and the average monthly income of families were the influencing factors in the family resilience score.Keywords: congenital pseudarthrosis of the tibia, family resilience, family characteristics, influencing factor